Co-ownership shares in condominium - A comparative analysis for selected civil law jurisdictions - Cagdas, Volkan; Paasch, Jesper M.; Paulsson, Jenny; Ploeger, Hendrik; Kara, Abdullah (ELSEVIER SCI LTD, 2020)
Condominium is a special and relatively new type of property right emerged in the last century to be a remedy for the management problems in multi-unit buildings. There are many types of condominium regimes, as described in EUI (2005), UNECE (2005) and van der Merwe (2016) The common elements include: (a) Individual right to an apartment, (b) co-ownership (joint ownership) of the common property or the whole property, and (c) membership of an incorporated or unincorporated owners' association (van der Merwe, 2015, p. 5). The ownership shares in the common property are here referred to as co-ownership shares; yet, alternative terms include ownership fraction, condominium share, participation quota, share value, and unit entitlement. Generally, these shares will determine the proportional contribution to the common expenses and the share of common profits, as well as the voting power of each condominium unit owner in the administration of the condominium. The most common approaches to the determination of the co-ownership shares are based on equality, relative size or relative value of each condominium unit, or a combination of such (van der Merwe, 1994, p. 57-58). The literature presents detailed descriptions and comparative analysis related to condominium systems in different jurisdictions (e.g. van der Merwe, 2015; 2016; Paulsson, 2007; EUI, 2005; UNECE, 2005); however, the procedural aspects related to the allotment of co-ownership shares still need to be further investigated. This article aims to describe condominium systems in the Netherlands, Sweden and Turkey, and compare legal provisions and procedures related to the allotment of co-ownership shares in these jurisdictions. The main purpose is to clarify the methodologies behind the determination of the co-ownership shares in national systems to bring new insights to countries, which are trying to revise their national provisions.
Keywords: Condominium; Co-ownership share; Ownership fraction; Participation quota; Share value; Unit entitlement; Environmental Sciences & Ecology